Susceptibility of primary cultured cells from the lymphoid organ of Penaeus monodon to Monodon Baculovirus (MBV) and White Spot Syndrome Virus (WSSV) - Catap, Elena S. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2008)
A primary cell culture system, susceptible to monodon baculovirus (MBV) and white spot syndromevirus (WSSV), was developed from the lymphoid organ of Penaeus monodon. Lymphoid organs fromshrimps (15–20 g) were dissected out and then placed in 2X Leibovitz-15 (L-15) medium with antibiot-ics (1 h) and subsequently minced. Four to five fragments were seeded in each well of a 24-well cultureplate and incubated in supplemented 2X L-15. The plates were incubated at 28 ºC in normal atmo-spheric condition. The basal culture medium was not supplemented with growth factors such asepidermal growth factor (EGF), fibroblast growth factor (FGF) or interleukin-2 (IL-2), but results showedexcellent cell proliferation and migration. Cells were 80% confluent after 4–6 d of culture, with predomi-nantly fibroblast-like type of cells, which were eventually overgrown with epithelioid type of cells after7 d of culture. The cell monolayers lasted for 3–4 wk with regular replacement of the growth medium.Subsequent experiments showed that MBV and WSSV replicated in the primary lymphoid cell cultures.Seven-day-old cell monolayers inoculated with two-fold dilutions of viral suspensions of either MBV orWSSV exhibited localized cytopathic effects (CPE) after 1–2 d of incubation at 28 ºC. Early CPE showedthe presence of highly refractile bodies and cell shrinkage; advanced cellular degeneration was ob-served after 3-4 d incubation, especially in monolayers which were inoculated with the higher viraldilutions. Significant cellular degeneration took a longer time to develop in cells inoculated with thelowest dilutions of WSSV. Polymerase chain reaction (PCR) assays were done to confirm MBV andWSSV infection of the cells. Positive MBV and WSSV infections were detected in all samples, except inthose inoculated with the lowest viral dilutions, at the nested PCR step only. Subsequent passages (2ndand 3rd) of harvested cell suspension on cultured lymphoid cells likewise produced CPE from day-3post-inoculation. This further confirms viral susceptibility and replication in the primary cultured lym-phoid cells.